2022
DOI: 10.5194/amt-15-1811-2022
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation inside proton-transfer-reaction-based mass spectrometers limits the detection of ROOR and ROOH peroxides

Abstract: Abstract. Proton transfer reaction (PTR) is a commonly applied ionization technique for mass spectrometers, in which hydronium ions (H3O+) transfer a proton to analytes with higher proton affinities than the water molecule. This method has most commonly been used to quantify volatile hydrocarbons, but later-generation PTR instruments have been designed for better throughput of less volatile species, allowing detection of more functionalized molecules as well. For example, the recently developed Vocus PTR time-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…However, different online instruments may have different sensitivities toward POs. For example, fragmentation could occur for both ROOH and ROOR′ types of POs due to the excess energy of protonated ions coming from the charge-transfer process during the PTR-TOF measurement . The stability of ions with different functionalities in various types of CIMS needs further investigations in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, different online instruments may have different sensitivities toward POs. For example, fragmentation could occur for both ROOH and ROOR′ types of POs due to the excess energy of protonated ions coming from the charge-transfer process during the PTR-TOF measurement . The stability of ions with different functionalities in various types of CIMS needs further investigations in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the high electric field in the ionization region produces protonated ions with high excess energy that are subject to strong decompositions, evidence from both laboratory experiments using PTR-TOF-MS and quantum chemical calculations revealed that the proton-transferring process may induce the decomposition of most POs. 257 Caution should be taken while measuring and interpreting atmospheric POs using PTR-TOF-MS. Recently, combining the NO 3 − chemical ionization source and a high-resolution Orbitrap MS (CI-Orbitrap), Riva et al 258,259 showed a similar sensitivity and selectivity of CI-Orbitrap with CI-APi-TOF using the nitrate ionization scheme, which has a resolution of ≥140,000 at m/z 200.…”
Section: Online Mass Spectrometric Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first provide an overview of the PMF algorithm before describing the overall cataloging approach. In this work, the term "analyte" is used to refer to a chromatographic peak (e.g., a chromatographic "feature") with a unique mass spectrum and retention time whether it has a known definitive identification or not, following the usage of this term in other studies (Amigo et al, 2010;Grace et al, 2019;Isaacman-VanWertz et al, 2017, 2021Li et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For the selectively deuterated samples, we can inspect their purity using PTR mass spectrometer data. As PTR instruments are known to induce isomerisation and fragmentation of the protonated molecules (Tani et al, 2003;Li et al, 2022), we expect that the observed level of deuteration in the PTR mainly provides a lower limit for the purity. The PTR measurements suggested that over 88 % of the measured a-pinene in our chamber contained exactly the number of D-atoms specified, verifying that the samples are very pure and in-line with the observed purity determined using 1 H NMR spectroscopy (see section 2.1).…”
Section: Interpreting the Mass Spectramentioning
confidence: 99%